2017
DOI: 10.1039/c6gc03139k
|View full text |Cite
|
Sign up to set email alerts
|

Controlling reactivity through liquid assisted grinding: the curious case of mechanochemical fluorination

Abstract: We have identified an example of a mechanochemically milled organic reaction where liquid-assisted grinding controls the selectivity, such a phenomenon has not been reported/observed before.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(88 citation statements)
references
References 44 publications
(5 reference statements)
1
84
0
1
Order By: Relevance
“…Stoichiometric selectivity in organic mechanosynthesis of: a) thioureas; [87] b) salicylaldimines; [88] c) fluorinated b-diketones. [89] Angewandte Chemie carboxylic and boronic acids using H 2 17 O, [94] while Lukin et al demonstrated rapid deuteration with D 2 O. [95]…”
Section: Benefits Of Solvent-free Environmentmentioning
confidence: 99%
“…Stoichiometric selectivity in organic mechanosynthesis of: a) thioureas; [87] b) salicylaldimines; [88] c) fluorinated b-diketones. [89] Angewandte Chemie carboxylic and boronic acids using H 2 17 O, [94] while Lukin et al demonstrated rapid deuteration with D 2 O. [95]…”
Section: Benefits Of Solvent-free Environmentmentioning
confidence: 99%
“…It was found that many reactions occur much faster as in solution, they can be performed under milder conditions, and the product is isolated in higher yields, compared to the corresponding reaction in solution. [17] Similar process improvements under mechanochemical conditions were achieved for a variety of reactions, for example the amidation of aldehydes, [18] the fluorination of 1,3-diketones, [19] the Michael addition, [20,21] the Knoevenagel condensation, [22] and the Morita-Baylis-Hillman reaction. The reactions were over in 4 h, yielding the products in very good to excellent yield (76-95 %).…”
Section: Mechanochemistry In Organic Synthesismentioning
confidence: 75%
“…In 2016, Browne and co-workers reported selective mechanochemical fluorination of 1,3-dicarbonyl compounds using selectfluor [ 101 – 102 ]. They could control the selectivity of the reaction through LAG using ACN (≈10% v/v of total materials) to get predominantly mono-fluorinated product over difluorinated derivatives ( Scheme 27 ).…”
Section: Reviewmentioning
confidence: 99%